HUBUNGAN FAKTOR SOSIO DEMOGRAFI DENGAN PEMILIHAN METODE KONTRASEPSI PADA WANITA USIA SUBUR (WUS) - Wulandari, Yunita Dwi; Yunaida, Yunaida; Marhamah, Mera; Kumala, Anes Patria (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The use of contraception aims to fulfill everyone's reproductive rights, by helping to plan when and how many children they want and prevent unwanted pregnancies. The proper use of contraceptives can also reduce the risk of maternal and infant mortality. This study aims to determine the relationship between socio-demographic factors and contraceptive selection. The design of this study is quantitative with a cross sectional study approach. The sample in this study was all women of childbearing age who were sexually active, sampling using the purposive sampling technique totaled 99 people. Data were obtained by interviews using questionnaires. The results showed that there was a significant relationship between age (p=0.022) and education level (p=0.015) and there was no relationship between occupation (p=0.167) and long-term contraceptive selection. Health service institutions must further improve the quality of counseling and long-term contraceptive services, so that they can attract the interest of the public in particular